Pixxaro Alone and in Combination for Weed Control in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to compare Pixxaro (halauxifen/fluroxypyr) alone and in combinations for weed control in fallow. Pixxaro alone was equal to or better than Banvel, Starane Ultra, or glyphosate alone for kochia control. However, the best kochia control occurred when these herbicides were mixed in various combinations. Similarly, Pixarro controlled flixweed equally as well as Banvel, Starane Ultra, or glyphosate at 7 days after treatment but flixweed control was complete regardless of herbicide later in the season.
Keywords: Herbicide-resistant kochia